Creep Characteristic of Rubber on Elastohydrodynamic Lubrication of Water-lubricated Rubber Bearing - Zhou Yabo; Wang Youqiang; Long Shenwen; Wei Cong (Jixie chuandong)
Considering the creep characteristics of the rubber bearing material,the infinite line contact model of the water-lubricated bearing is established,based on the Kelvin model and the three-parameter model,the elastohydrodynamic lubrication of water-lubricated rubber bearings is analyzed. The effects of creep of rubber bearing on the pressure and film thickness of the lubricating membrane are obtained. The effects of the central pressure,the central film thickness and the minimum film thickness under the influence of the two models are analyzed and contrasted. The results show that the creep characteristics of the rubber bearing has great influence on the pressure and the thickness of the lubricating membrane. Under the two creep models,the pressure of the lubricating film decreases with the creep time,and the thickness of the lubricating film increases with the creep time,at the same time the contact area is increasing to the end of the constant value. The central pressure increases with the creep time and tends to be stable. The minimum film thickness decreases with the creep time and then decreases to the steady value. After the creep stabilization,the pressure and film thickness of the two models are larger than those of the rubber bearing as the linear elastomer. Compared with the previous work,the three-parameter solid model can describe the lubricating performance of the rubber bearing better than the Kelvin model.